Tissue-Specific Methylation of Long Interspersed Nucleotide Element-1 of Homo Sapiens (L1Hs) During Human Embryogenesis and Roles in Neural Tube Defects - Wang, L.; Chang, S.; Guan, J.; Shangguan, S.; Lu, X.; Wang, Z.; Wu, L.; Zou, J.; Zhao, H.; Bao, Y.; Qiu, Z.; Niu, B.; et al. (Current Molecular Medicine, 2015)
Epigenetic regulation of long interspersed nucleotide element-1 (LINE-1) retrotransposition events plays crucial roles during early development. Previously we showed that LINE-1 hypomethylation in neuronal tissues is associated with pathogenesis of neural tube defect (NTD). Herein, we further evaluated LINE-1 Homo sapiens (L1Hs) methylation in tissues derived from three germ layers of stillborn NTD fetuses, to define patterns of tissuespecific methylation and site-specific hypomethylation at CpG sites within an L1Hs promoter region. Stable, tissue-specific L1Hs methylation patterns throughout three germ layer lineages of the fetus, placenta, and maternal peripheral blood were observed. Samples from maternal peripheral blood exhibited the highest level of L1Hs methylation (64.95%) and that from placenta showed the lowest (26.82%). Between samples from NTDs and controls, decrease in L1Hs methylation was only significant in NTD-affected brain tissue at 7.35%, especially in females (8.98%). L1Hs hypomethylation in NTDs was also associated with a significant increase in expression level of an L1Hs-encoded transcript in females (r = -0.846, p = 0.004). This could be due to genomic DNA instability and alternation in chromatins accessibility resulted from abnormal L1Hs hypomethylation, as showed in this study with HCT-15 cells treated with methylation inhibitor 5-Aza.
Keywords: genomic instability